Three essays on empirical asset pricing - ZENG, Ming (Institutional Knowledge at Singapore Management University, 2018)
This thesis consists of three chapters. In Chapter1, I show that returns to currency carry and momentum strategies are compensations for the risk of US monetary policy uncertainty (MPU), with risk exposures explaining 96% of their cross-sectional return variations. The findings are consistent with an intermediary-based exchange rate model. Higher MPU triggers position unwinding by the intermediary, which decreases there turns of currency with high-interest rate or appreciation, while that with low-interest rate or depreciation earns positive returns. Different responses stem from the long and short behavior of the intermediary. The explanatory power of US MPU risk is robust and unrelated to commonly used risk factors.